Efficiency improvement of 50 Hz wireless photovoltaic power transfer using magnetic relay - Irwanto, Muhammad; Baharudin, Nor Hanisah; Nugraha, Yoga Tri; Nisja, Indra (Institute of Advanced Engineering and Science, 2025)
A photovoltaic direct current (DC) power can be changed into AC power using an inverter. The inverter must be connected to an alternating current (AC) load using wire, which has drawbacks in terms of air space, wire cost, and an unattractive view of the sky. It is appropriate to suggest a wireless power transfer (WPT) system concept to replace the use of wires in the transfer of electrical power. The WPT system has been conducted by the previous researchers, but it is still in the frequency system of hundred, kilo, mega or gigahertz, thus it can only be applied on DC load after rectifying it, but cannot be applied for a normal AC load, also its distance is relative near. The modelling of wireless photovoltaic power transfer (WPVPT) with a 50 Hz system frequency is presented in this work. The four modelling components that create the WPVPT system are models of the PV module, the transmitter circuit, the magnetic relay, and the receiver circuit. The findings indicate that the efficiency of the proposed WPVPT system is 71.27% without a magnetic relay and 72.82% with a magnetic relay. It suggests that the use of magnetic relay can improve the WPVPT system's efficiency.